Buckling characteristics of externally pressurised toroidal shell. (13th September 2020) - Zhu, Y.; Chen, B.; Zhao, B.; Zhao, X.; Tang, W.; Wang, X.
ABSTRACT: This study investigates the buckling characteristics of toroidal shells with a closed circular cross-section and loaded by static external pressure. With the thickness imperfection considered as the initial geometrical imperfection, the nonlinear buckling numerical calculation of the toroidal shells is discussed in detail. The finite element model was used for the toroidal shell and validated accordingly. The numerical results of mean thickness, variable thickness, and mode imperfection, which was introduced to simulate the real thickness imperfection without the initial thickness imperfection being specified, were compared with the experimental results. In addition, four laboratory-scale models were manufactured and tested. Each of models was assembled by welding four 90° 304 stainless steel elbows. The geometry, toroidal shell thickness, buckling load, and final collapsed mode were measured for each toroidal shell; the material properties of the corresponding sheets were also measured. The results of the theoretical, numerical, and experimental investigations are compared in this paper.